Comparative Life Cycle Assessment of a Thai Island's diesel/PV/wind hybrid microgrid. (August 2015) - Smith, Cameron; Burrows, John; Scheier, Eric; Young, Amberli; Smith, Jessica; Young, Tiffany; Gheewala, Shabbir H.
Abstract: Hybrid microgrid systems are an emerging tool for rural electrification due in part to their purported environmental benefits. This study uses Life Cycle Assessment (LCA) to compare the environmental impacts of a diesel/PV/wind hybrid microgrid on the island of Koh Jig, Thailand with the electrification alternatives of grid extension and home diesel generators. The impact categories evaluated are: acidification potential (kg SO2 eq), global warming potential (kg CO2 eq), human toxicity potential (kg 1.4 DCB eq), and abiotic resource depletion potential (kg Sb eq). The results show that the microgrid system has the lowest global warming and abiotic resource depletion potentials of all three electrification scenarios. The use phase of the diesel generator and the extraction of copper are shown to significantly contribute to the microgrid's environmental impacts. The relative environmental impacts of the grid extension scenario are found to be proportional to the distance required for grid extension. Across all categories except acidification potential, the impacts from the home diesel generators are the largest. Sensitivity analyses show that maximizing the renewable energy fraction does not necessarily produce a more environmentally sustainable electrification scenario and that the diesel generator provides versatility to the system by allowing power production to be scaled significantly before more technology is needed to meet demand. While the environmental benefits of the microgrid increase as the installation community becomes more isolated, the choice of electrification scenario requires assigning relative importance to each impact category and considering social and economic factors.